Fashion and modernism - Kollnitz, Andrea 1970-; Wallenberg, Louise 1970- (Bloomsbury Visual Arts, 2019)
"Art and fashion have long gone hand in hand, but it was during the modernist period that fashion first gained equal value to - and took on the same aesthetic ideals as - painting, film, photography, dance, and literature. Combining high and low art forms, modernism turned fashion designers into artists and vice versa. Bringing together internationally renowned scholars across a range of disciplines, this vibrant volume explores the history and significance of the relationship between modernism and fashion and examines how the intimate connection between these fields remains evident today, with contemporary designers relating their work to art and artists problematizing fashion in their works. With chapters on a variety topics ranging from Russian constructionism and clothing to tango and fashion in the early 20th century, Fashion and Modernism is essential reading for students and scholars of fashion, dress history, and art history alike. Contributors: Patrizia Calefato, Caroline Evans, Ulrich Lehmann, Astrid Söderbergh Widding, Alessandra Vaccari, Olga Vainshtein, Sven-Olov Wallenstein."--Bloomsbury Publishing
Keywords: Geschichte 1830-1960; Fashion & society; Clothing and dress / History; Fashion and art; Modernism (Art); Kunst; Moderne; Mode; Aufsatzsammlung